Mid-infrared photon sensing using InGaN/GaN nanodisks via intersubband absorption - Xing, Zhang; Akter, Afroja; Kum, Hyun S.; Baek, Yongmin; Ra, Yong Ho; Yoo, Geonwook; Lee, Kyusang; Mi, Zetian; Heo, Junseok (Scientific Reports, 2022)
Intersubband (intraband) transitions allow absorption of photons in the infrared spectral regime, which is essential for IR-photodetector and optical communication applications. Among various technologies, nanodisks embedded in nanowires offer a unique opportunity to be utilized in intraband devices due to the ease of tuning the fundamental parameters such as strain distribution, band energy, and confinement of the active region. Here, we show the transverse electric polarized intraband absorption using InGaN/GaN nanodisks cladded by AlGaN. Fourier transform infrared reflection (FTIR) measurement confirms absorption of normal incident in-plane transverse electric polarized photons in the mid-IR regime (wavelength of ~ 15 μm) at room temperature. The momentum matrix of the nanodisk energy states indicates electron transition from the ground state s into the px or py orbital-like excited states. Furthermore, the absorption characteristics depending on the indium composition and nanowire diameter exhibits tunability of the intraband absorption spectra within the nanodisks. We believe nanodisks embedded nanowires is a promising technology for achieving tunable detection of photons in the IR spectrum.